The Evolutionary Logic and Ideological Connotations of Traditional Medical Confidentiality Principles - Xinzhi JIANG; Yihang ZHANG; Ziying YANG; Xiaqiang WANG (Yixue yu zhexue, 2025)
Traditional Chinese medical confidentiality ideology was deeply rooted in the fertile soil of Chinese traditional culture, forming a unique cultural system of medical confidentiality thought. The evolution of this thought was influenced by many complex factors, with two primary aspects playing significant roles. The first was the introduction of Confucianism into medical practice which promoted an empathetic approach toward patients. The second was the development of traditional Chinese surgical practices which highlighted the importance of protecting patients' privacy. The traditional medical confidentiality thought embodied the values of being "people-oriented" and the pursuit of self-cultivation by being modest and humble. By acknowledging confidentiality responsibilities, fulfilling obligations, and improving standards, traditional medical confidentiality can be more effectively applied to modern clinical practice.